A loss-of-function p.G191R variant in the anionic trypsinogen (PRSS2) gene in Japanese patients with pancreatic disorders. Issue 6 (3rd December 2008) - Kume, K; Masamune, A; Takagi, Y; Kikuta, K; Watanabe, T; Satoh, K; Satoh, A; Hirota, M; Hamada, S; Shimosegawa, T
Abstract : Objective: There is a concept that pancreatitis results from an imbalance of proteases and their inhibitors within the pancreatic parenchyma. It has been recently shown that a loss-of-function variant, c.571G>A (p.G191R), in the anionic trypsinogen ( PRSS2 ) gene protects against chronic pancreatitis in European populations. Here we examined the association of the p.G191R variant with pancreatic disorders in Japan. Methods: Genomic DNA was prepared from 378 healthy controls and 604 patients with pancreatic disorders (241 patients with chronic pancreatitis, 174 with acute pancreatitis, and 189 with pancreatic neoplasm). Mutational analysis of the PRSS2 gene was performed by polymerase chain reaction–restriction fragment length polymorphism and direct sequencing. Results: The heterozygous p.G191R variant was found in three of 241 (1.2%) patients with chronic pancreatitis, in seven of 174 (4.0%) patients with acute pancreatitis, and in 12 of 189 (6.3%) patients with pancreatic neoplasm. The p.G191R variant was found in 25 (two were homozygous and 23 were heterozygous) of 378 (6.6%) healthy controls. The p.G191R frequency in patients with chronic pancreatitis was lower than that in healthy controls (p = 0.001; odds ratio (OR) 0.178; 95% confidence interval (CI) = 0.057 to 0.561). The p.G191R frequency was lower in patients with alcoholic (0.9%; p = 0.015; OR, 0.132; 95% CI, 0.022 to 0.779) and idiopathic (1.0%; p = 0.025; OR, 0.144; 95% CI, 0.025 to 0.851) chronic pancreatitis than that in healthy controls. There were no statistical differences in the p.G191R frequency between healthy controls and patients with acute pancreatitis or with pancreatic neoplasm. Patients with alcoholic acute pancreatitis (n = 59) had no variant carrier, and the p.G191R frequency was lower than that in healthy controls (p = 0.035). Conclusion: The p.G191R variant protected against alcoholic and idiopathic chronic pancreatitis as well as alcoholic acute pancreatitis in Japan.